Colonization of Serendipita indica promotes resistance against Spodoptera exigua in onion (Allium cepa L.) - Roylawar, Praveen; Khandagale, Kiran; Nanda, Satyabrata; Soumia, Parakkattu Sulochanan; Jadhav, Sangita; Mahajan, Vijay; Gawande, Suresh (Frontiers in Microbiology, 2023)
Plant-endophyte symbiosis influences plant defense and growth. Serendipita Piriformospora indica is a root endophyte that promotes growth and induces tolerance against biotic and abiotic stress in plants. In this study, we examined the effect of PS. indica colonization on herbivore (Spodoptera exigua) resistance of onion (Allium cepa L.). We found that colonization of PS. indica in the roots of onion significantly reduced the feeding damage of leaves by S. exigua larvae, and also resulted in a reduction in weight gain of the larvae when fed on P. indica plants.This enhanced resistance is a result of modulation of antioxidant and defense enzymes/genes in the host by PS. indica mutualism. Specifically, the activities of enzymes such as Superoxide dismutase, guaiacol peroxidase, polyphenol oxidase, phenylalanine ammonia-lyase, and H2O2 content were significantly higher in the early stages of S. exigua feeding in the PS. indica colonized plants compared to the non-colonized counterparts. Similarly, defense genes also showed modulation in response to this tripartite interaction of onion -P. indicaS. indica mutualism and S. exigua herbivory. The hierarchical cluster analysis and principal component analysis indicated a clear difference in the onion biochemical responses, which is due to the P. indica symbiosis. Our investigation demonstrates that onion-PS. indica symbiosis significantly decreases chewing injury by efficiently modulating antioxidant and defense enzyme activities and gene expression in response to S. exigua herbivory. Therefore, PS. indica can be used as a potential biocontrol agent for sustainable management of this important pest of Alliums